Optimization of a natural low-calorie antioxidant tea prepared from purple corn (Zea mays L.) cobs and stevia (Stevia rebaudiana Bert.) - Díaz-García, A. (2021)
The authors acknowledge INNOVATE-PERU for funding the project “Development of purple corn filters with quince and stevia leaves as a proposal for a fruit infusion with high antioxidant capacity, naturally sweetened and with a high level of pleasure in LECOLE PRODUITS S.A.C.'': contract 027-INNOVATEPERU-PIEC1-2019. Also, A. DÍAZ-GARCÍA recognizes the scholarship from the Concytec-Banco Mundial project (Funds Award Agreement No. 02-2018-FONDECYT-BM), through its executing unit, Fondo Nacional de Desarrollo Científico, Tecnológico y de Innovación Tecnológica (Fondecyt).